Qualitative Characteristics of the Information Presented in the Financial Statements Prepared on the Basis of the International Public Sector Accounting Standards - Daskalov, Yasen (Research Papers, 2020)
The purpose of this report is to present the qualitative characteristics of the information presented in the financial statements of public sector entities in applying the International Public Sector Accounting Standards (IPSAS). A comparison of the qualitative characteristics in IACS and International Financial Reporting Standards has been made, with some major differences. The lack of standardization of public sector accounting in Bulgaria is sufficient to raise the question of the quality of the information presented in the financial statements of the public sector entities.